Possibilidades de atividades de comunicação emocional entre bebês: um estudo à luz da teoria histórico-cultural - Scudeler, Adriane Pereira Borges [UNESP] (2015)
This essay results from survey developed to the Education Post-Graduation Program of the Sciences and Philosophy College - Unesp - Câmpus Marília, São Paulo and to the Theory and Pedagogical Practices Search Line. It shows results from surveys arising from questions such as: how do babies at the age of one year old learn? How to establish relationships with adults and with other children? How do teachers of children should act so that they develop specifically human skills? From these questions, the following work presupposition emerged: at dealing with children and setting the we talk and listen to them, solving a problem or playing, we organize irreplaceable moments for intelligence and personality building in the early years of their life. Lead by this presupposition, the research had as its main goal to identify and understand the possibilities of emotional communication of children at the age from 4 to 12 months considering concrete educational conditions (space, time, materials, relationships), organized by the research partner daycare school teachers. The methodological procedures involved review of literature, pictures and taping of pedagogical practices. We defend that early childhood education should prioritize the children´s intelligence and personality building and development seeking the exercise of their multiple possibilities and ability to learn, and understand that teaching practices are materialized from emotional ties and relationships between adults and children, providing learning and cultural formation during childhood. From a theoretical viewpoint, the results emphasize that toddlers learn since they are born, under the appropriate living conditions and education. One of these learning processes is related to the emotional communication through the tears, smile, movements, gestures and babbling. The analysis pointed that babies learn from their experiences, the environment where they live, with other children